Sprayed wheel-traffic effects from late season applications on soybean yield. (FAVE Sección Ciencias Agrarias, 2024)
End-of-cycle diseases in soybean can cause significant defoliation and yield loss. The application of fungicides with a terrestrial sprayer must not only be economically viability, but the potential damage caused by the sprayer wheel track must be evaluated. The impact of the sprayer's footprint on yield loss depending on the time of sowing and the distance between crop lines is not well document. The objective of this study was to quantify and characterize the impact of the ground sprayer footprint in end-of-cycle applications and the effect of spacing between crop lines on soybean yield and grain loss. Sixteen batches with soybean crops were selected. Crops were planted at different row spacing and applied in favor or perpendicular/oblique to the planting line. Yield loss due to the sprayer wheel track was determined. Yield loss varied between 1.4 and 3.3%. The distance between sowing lines and the spraying direction seems to be the main variables that can affect the value of yield loss. The greater the width of the boom, the loss of performance is reduced since the number of passes is reduced. At the application time, it is important to consider the crop condition and the available technology that minimizes losses either due to diseases or due to the application.
Keywords: end-of-cycle diseases; agricultural tires; pos-emergent applications; fungicide; yield loss